ENTRE O OLHAR DO CUIDADO E A PATOLOGIZAÇÃO: UM ESTUDO SOBRE A REDE DE ATENÇÃO EM SAÚDE MENTAL À CRIANÇA E AO ADOLESCENTE - Teixeira, Denize Aparecida (2016)
Pathologization has been showing it's growth in contemporaneity, in the other hand, the critic about reproduction of pathologized children is gaining strenght trough a growing movement wich seeks to avoid that psychosocial matters be reduced to a biological process. It's known tha most part of the referralsto psychologic evaluation is originated in the school environment, where teachers find themselves anguished looking for answers for the difficulties showed by their students, may it be of behaviour order or learning. Qualitative research, has as samples components of the children and adolescent care system at the municipality, linked to the health departments, social assistence, education, culture, guardianship council, the president of CMDCA (Child and adolescent municipal council) and a teacher of the state education department. The individuals participating in the research were divided in three groups: Group I- Multi professional team(11 participants), Group II- pedagogical team (10 participants), group III- Management team (three participants). As for the data collection techniques, it included procedure such as documentary analysis, collective interview trough the composition of a focal group with teachers and another with a multiprofessional team, furthermore, the application of questionnaires to the participants of focal group and managers.The method of analysis, was the hermeneutic dialetic, in wich were elaborated two analysis categories, them being, Category I- the faces of a nonexistent system, wich showed characteristics of nonexistense as a system, taking shape with a set of compartmentalized equipments, appearing dismantled and closed at its disciplinarity. Category II- Construction of the system to new perspectives, new insight for the caring. In wich confirms indicators of the process of pathologization in the municipality, in wich lots of refferals show up to be inconsistent, beinf revealed as symptoms of a nonexistent system, wich manisfests itself at the pratic of (dis)regard. pointing out the necessity of articulation of the system trough intersectoriality and paradigm shift the interdisciplinar shows itself as the path to the constitution of a new service network with new perspectives, new sights for care.